Strategi Pengembangan Pendidikan Karakter dalam Kurikulum Sekolah Dasar - Resky Ananda Putri Erwinsyah; Muhammad Taufiq; Gusmaneli Gusmaneli (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This research aims to examine character education development strategies integrated into elementary school curriculum. Character education becomes an integral part of student personality formation that needs to be instilled from an early age. Through a descriptive qualitative approach, this research analyzes various strategies for implementing character education in curriculum, learning, and elementary school culture. The results show that character education development in elementary school curriculum can be carried out through four main strategies: (1) integration of character values in subjects, (2) development of character-based school culture, (3) learning based on traditional games containing local wisdom values, and (4) involvement of parents and community in character formation. The implementation of these strategies requires systematic planning, commitment from all education stakeholders, and continuous evaluation to ensure the achievement of character education goals.